Homelessness and Veteran Status in Relation to Nonfatal and Fatal Opioid Overdose in Massachusetts. Issue 4 (April 2021) - Jasuja, Guneet K.; Bettano, Amy; Smelson, David; Bernson, Dana; Rose, Adam J.; Byrne, Thomas; Berlowitz, Dan R.; McCullough, Megan B.; Miller, Donald R.
Abstract : Background: Compared with non-Veterans, Veterans are at higher risk of experiencing homelessness, which is associated with opioid overdose. Objective: To understand how homelessness and Veteran status are related to risks of nonfatal and fatal opioid overdose in Massachusetts. Design: A cross-sectional study. Participants: All residents aged 18 years and older during 2011–2015 in the Massachusetts Department of Public Health's Data Warehouse (Veterans: n=144, 263; non-Veterans: n=6, 112, 340). A total of 40, 036 individuals had a record of homelessness, including 1307 Veterans and 38, 729 non-Veterans. Main Measures: The main independent variables were homelessness and Veteran status. Outcomes included nonfatal and fatal opioid overdose. Results: A higher proportion of Veterans with a record of homelessness were older than 45 years (77% vs. 48%), male (80% vs. 62%), or receiving high-dose opioid therapy (23% vs. 15%) compared with non-Veterans. The rates of nonfatal and fatal opioid overdose in Massachusetts were 85 and 16 per 100, 000 residents, respectively. Among individuals with a record of homelessness, these rates increased 31-fold to 2609 and 19-fold to 300 per 100, 000 residents. Homelessness and Veteran status were independently associated with higher odds of nonfatal and fatal opioid overdose. There was a significant interaction between homelessness and Veteran status in their effects on risk of fatal overdose. Conclusions: Both homelessness and Veteran status were associated with a higher risk of fatal opioid overdoses. An understanding of health care utilization patterns can help identify treatment access points to improve patient safety among vulnerable individuals both in the Veteran population and among those experiencing homelessness. Abstract : Supplemental Digital Content is available in the text.